Implementasi Model Pembelajaran Problem Based Learning dalam Mata Pelajaran IPS Terpadu di SD/MI - Selvi Melani; Nurul Fadilah; Tria Aulia Maulidah; Oman Farhurrohman (Journal on Education, 2025)
Low student interest and learning outcomes in Integrated Social Studies subjects in Elementary Schools/Islamic Elementary Schools are often caused by conventional learning approaches and a lack of active student involvement. The Problem Based Learning (PBL) model offers a solution through contextual problem solving. This study aims to analyze the implementation of the PBL model in Integrated Social Studies learning in Elementary Schools/Islamic Elementary Schools and identify its impact on student learning outcomes. This study uses a literature study method by analyzing various relevant journal articles, books, and scientific publications published in 2018-2023. The results of the analysis show that the application of PBL in Integrated Social Studies is effective in improving students' conceptual understanding, critical thinking skills, collaboration, and learning motivation. PBL stages such as problem orientation, learning organization, independent inquiry, development and presentation of results, as well as analysis and evaluation, are successfully applied in the context of local problems close to students' lives.